Risk factors and trends in injury mortality in Rufiji Demographic Surveillance System, rural Tanzania from 2002 to 2007 - Ae-Ngibise, Kenneth Ayuurebobi (My University, 2010)
Background Worldwide, injuries are ranked among the leading causes of death and disability, killing over 5 million people and injuring over 50 million others globally. Approximately 90% of these deaths occur in developing countries. The burden and pattern of injuries in low-income countries are poorly known and not well studied. Few studies have been conducted on injury mortality and therefore this study can add to the scientific literature. Analyzing injury mortality in rural Tanzania can assist African countries to develop intervention programmes and policy reform to reduce the burden caused by injuries. Objectives The objective of this study was to identify the risk factors and trend in injury mortality in the Rufiji Demographic Surveillance Area in rural Tanzania from 2002-2007. Specifically, the study would identify and describe the types and trends in injury mortality, calculate the crude death rates of injury mortality by gender, SES and age groups, describe the risks factors associated with injury mortality, and measure association between the risk factors and injury mortality. Methods Rufiji HDSS data used included people aged 1 year and older from 2002-2007. Verbal Autopsy data was used to determine the causes of death which was based on the tenth revision of the International Classification of Diseases (ICD 10) recommended by WHO. Injury Crude death rates (ICDR) were calculated by dividing number of deaths in each year by person years observed and multiplying by 100,000. Principal Component Analysis (PCA) was used to construct household wealth index using household characteristics and assets ownership. Also trend test analysis was done to assess a linear relationship in the injury mortality rates across the six year period. Poisson regression was used to investigate v association between risk factors and injury mortality and all tests for significant associations were based on p-values at 5% significance level and a 95% confidence interval. Results The overall injury crude mortality rate was 33.4 per 100,000 PYO. Injuries contributed 4% of total mortality burden with statistical significant association between gender, age and occupation. Mortality rate was higher for males [Adjusted IRR=3.04, P=0.001, 95% CI (2.22 - 4.17)]. The elderly (65+) were 2.8 times more likely to die from injuries compared to children [Adjusted IRR=2.83, P=0.048, 95% CI (1.01 - 7.93)]. The unemployed, casual workers, the retired, and farmers all had an increased risk of dying from injuries compared to students (P<0.005). Most injury deaths were due to road traffic accidents (28%), unspecified external injuries (20%), drowning (16%), burns (9%), accidental poisoning (8%), homicidal (8%) and animal attack (5%). Conclusion The contribution of injury to mortality burden in the Rufiji Demographic Surveillance Area was relatively low. However, there is the need to institute measures that would help prevent injuries. Life saving interventions such as road safety education, regular road maintenance, rapid response to accidents, use of life jackets for fishermen and recreational swimmers are very necessary in preventing injuries. Also, proper fishing practices should be imparted to the populace as precautionary measures to reduce the burden of injury mortality.
Research report in partial fulfillment for the degree of MSc (Med), Population Based Field Epidemiology, University of the Witwatersrand
Keywords: Tanzania; injury mortality